A bioinspired porous-designed hydrogel@polyurethane sponge piezoresistive sensor for human–machine interfacing. Issue 45 (15th November 2021) - Shen, Junhao; Guo, Yixin; Zuo, Shaohua; Shi, Fuwen; Jiang, Jinchun; Chu, Junhao
Abstract : A hydrogel@PU piezoresistive sensor with a compressible porous conductive layer has good cycle stability under 80% strain. Abstract : Conductive coating sponge piezoresistive pressure sensors are attracting much attention because of their simple production and convenient signal acquisition. However, manufacturing sponge-structure pressure-sensing materials with high compressibility and wide pressure detection ranges is difficult because of the instability of rigid and brittle conductive coatings at large strains. Herein, a tough conductive hydrogel@polyurethane (PU) sponge with a porous design is prepared via immersion of a polyurethane sponge in a low-cost and biocompatible polyvinyl alcohol (PVA)/glycerin (Gl)/sodium chloride (NaCl) solution. The sensor based on the hydrogel/elastomer sponge composite material exhibits a compressible range of 0–93%, a pressure detection range of 100 Pa–470.2 kPa, and 10 000-cycle stability (80% strain) because of the compressibility, flexibility, and toughness of the porous hydrogel coating. Benefiting from the resistance change mechanism of microporous compression, the sensor also exhibits a wide range of linear resistance changes, and the corresponding sensitivity and gauge factor (GF) are −0.083 kPa −− (100 Pa–10.0 kPa) and −1.33 (1–60% strain), respectively. Based on its flexibility, compressibility, and wide-ranging linear resistance changes, the proposed sensor has huge potential application in human activity monitoring, electronic skin, and wearable electronic devices.